Análisis de la utilidad de las escalas pronósticas en la identificación temprana de sepsis en pacientes hospitalizados en la UCI. - Garófalo Guillín, María José (2024)
In this research, the usefulness of prognostic scales for the early identification of sepsis in patients hospitalized in the Intensive Care Unit (ICU) is evaluated through a systematic literature review. The methodology applied consisted of the selection and analysis of bibliographic research that addressed the application of scales such as SOFA, qSOFA, NEWS, and SIRS in the early detection of sepsis. The results indicated that the SOFA scale is the most accurate tool to predict mortality in critically ill patients. At the same time, qSOFA was helpful in the rapid assessment of sepsis in emergency settings. NEWS was shown to be effective in monitoring respiratory deterioration, especially in cases of COVID-19, while SIRS was more sensitive but less specific compared to qSOFA. The discussion reflected that the early implementation of scales such as SOFA and NEWS can significantly improve clinical outcomes, reducing mortality and complications in the ICU. The overall conclusion suggests that the use of SOFA in combination with faster scales such as qSOFA in emergency settings results in an effective approach for the comprehensive management of sepsis. As a recommendation, it is suggested to standardize the use of these scales in clinical protocols, train health personnel in their proper application, and improve the integration of advanced technology to optimize diagnostic accuracy and clinical outcomes.